Inactivation of H(+)-ATPase Participates in the Influence of Variation Potential on Photosynthesis and Respiration in Peas - Yudina, Lyubov (Plants (Basel), 2020)
Local damage (e.g., burning, heating, or crushing) causes the generation and propagation of a variation potential (VP), which is a unique electrical signal in higher plants. A VP influences numerous physiological processes, with photosynthesis and respiration being important targets. VP generation is based on transient inactivation of H(+)-ATPase in plasma membrane. In this work, we investigated the participation of this inactivation in the development of VP-induced photosynthetic and respiratory responses. Two- to three-week-old pea seedlings (Pisum sativum L.) and their protoplasts were investigated. Photosynthesis and respiration in intact seedlings were measured using a GFS-3000 gas analyzer, Dual-PAM-100 Pulse-Amplitude-Modulation (PAM)-fluorometer, and a Dual-PAM gas-exchange Cuvette 3010-Dual. Electrical activity was measured using extracellular electrodes. The parameters of photosynthetic light reactions in protoplasts were measured using the Dual-PAM-100; photosynthesis- and respiration-related changes in O(2) exchange rate were measured using an Oxygraph Plus System. We found that preliminary changes in the activity of H(+)-ATPase in the plasma membrane (its inactivation by sodium orthovanadate or activation by fusicoccin) influenced the amplitudes and magnitudes of VP-induced photosynthetic and respiratory responses in intact seedlings. Decreases in H(+)-ATPase activity (sodium orthovanadate treatment) induced fast decreases in photosynthetic activity and increases in respiration in protoplasts. Thus, our results support the effect of H(+)-ATPase inactivation on VP-induced photosynthetic and respiratory responses.